Epigenetic mechanisms of major depression: Targeting neuronal plasticity. Issue 4 (26th December 2017) - Uchida, Shusaku; Yamagata, Hirotaka; Seki, Tomoe; Watanabe, Yoshifumi
Abstract : Major depressive disorder is one of the most common mental illnesses as it affects more than 350 million people globally. Major depressive disorder is etiologically complex and disabling. Genetic factors play a role in the etiology of major depression. However, identical twin studies have shown high rates of discordance, indicating non‐genetic mechanisms as well. For instance, stressful life events increase the risk of depression. Environmental stressors also induce stable changes in gene expression within the brain that may lead to maladaptive neuronal plasticity in regions implicated in disease pathogenesis. Epigenetic events alter the chromatin structure and thus modulate expression of genes that play a role in neuronal plasticity, behavioral response to stress, depressive behaviors, and response to antidepressants. Here, we review new information regarding current understanding of epigenetic events that may impact depression. In particular, we discuss the roles of histone acetylation, DNA methylation, and non‐coding RNA. These novel mechanisms of action may lead to new therapeutic strategies for treating major depression.